2011
DOI: 10.1007/s10526-011-9341-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three basidiomycetous fungal species on soil-borne, foliage and fruit-damaging phytopathogens in laboratory experiments

Abstract: The effect of three basidiomycetous fungi, Meira geulakonigii, M. argovae and Acaromyces ingoldii on strains of seven phytopathogenic fungal species was assayed in the laboratory. The phytopathogens were placed on dialysis membranes covering media in which the basidiomycetous fungi were formerly cultured. A. ingoldii inhibited the growth of all phytopathogens tested, whereas Meira spp. suppressed their growth to a lesser extent. Upon being returned to extract-free media, all phytopathogens resumed their growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Acaromyces ingoldii is an endophytic fungus belonging phylogenetically to the Cryptobasidiaceae, Exobasidiomycetidae (Ustilaginomycetes, Basidiomycota), and has been isolated from diverse habitats worldwide, from mite cadavers from the coastal plain of Israel [1][2][3][4], to marine sediment in the South China Sea [5]. Boekhout et al [1] reported a high mortality rate among several mite species after inoculation with A. ingoldii.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acaromyces ingoldii is an endophytic fungus belonging phylogenetically to the Cryptobasidiaceae, Exobasidiomycetidae (Ustilaginomycetes, Basidiomycota), and has been isolated from diverse habitats worldwide, from mite cadavers from the coastal plain of Israel [1][2][3][4], to marine sediment in the South China Sea [5]. Boekhout et al [1] reported a high mortality rate among several mite species after inoculation with A. ingoldii.…”
Section: Introductionmentioning
confidence: 99%
“…Given A. ingoldii toxicity towards mites [3], it was suggested that its presence in the nesting cavity could attack either feather mites on the birds, or alternatively, mites that feed on fungi that facilitate cavity excavation through wood decay [6]; the possibility also exists that A. ingoldii may directly inhibit the growth of fungi that are "detrimental" to the birds. Laboratory studies with fungal cultures have shown secretions from A. ingoldii inhibit the growth of phytopathogens found in soil, foliage and fruit [4].…”
Section: Introductionmentioning
confidence: 99%
“…These species have been isolated from plant tissues, fruits, and mites. These Meira species exhibit promising antagonistic activities against a wide spectrum of fungal and bacterial plant diseases [10]. However, only one compound, argovin (1), has been reported from the genus Meira [11].…”
Section: Introductionmentioning
confidence: 99%
“…We also reported that another species, Meira geulakonigii Boekhout, Scorzetti, Gerson & Sztejnberg, reduced cucumber powdery mildew growth and killed mites in the laboratory as well as in the field, including Phyllocoptruta oleivora (Ashmead) (Acari: Eriophyidae), the citrus rust mite (CRM), a major pest of citrus (Argov et al., 2002). Both Meira species, along with Acaromyces species, showed promising antagonistic activities against a broad range of fungal and bacterial plant diseases (Kushnir et al., 2011). We also showed that all three fungi affect their acarine and fungal targets by secreted toxins; metabolites that had hitherto neither been analyzed nor identified (Sztejnberg et al., 2004; Paz et al., 2007a,b; Kushnir et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Both Meira species, along with Acaromyces species, showed promising antagonistic activities against a broad range of fungal and bacterial plant diseases (Kushnir et al., 2011). We also showed that all three fungi affect their acarine and fungal targets by secreted toxins; metabolites that had hitherto neither been analyzed nor identified (Sztejnberg et al., 2004; Paz et al., 2007a,b; Kushnir et al., 2011). Thus its mode of action is similar to that of Pseudozyma flocculosa (Traquair, LA Shaw & Jarvis) Boekhout & Traquair (Ustilaginaceae), a related species (in terms of phylogeny, ecological niche, and morphology), which is active against fungal diseases (Cheng et al., 2003).…”
Section: Introductionmentioning
confidence: 99%